A review of the statistical analysis of randomised controlled trials conducted within OCTRU - Alexander Ooms; Caitlin Waldron; Daphne Kounali; Ioana R. Marian; M. Sofia Massa; Nicholas Peckham; Matthew Parkes; Elizabeth Conroy; Jonathan A. Cook (Trials)
Abstract Introduction Despite a proliferation of statistical methodologies and developments within randomised controlled trials (RCTs) in recent decades, it is unclear which approaches are being implemented in practice. Oxford Clinical Trials Research Unit (OCTRU) is a UK Clinical Research Collaboration (UKCRC) registered Clinical Trials Unit (CTU) that has been operational since 2013 based in the Nuffield Department of Orthopaedics, Rheumatology and Musculoskeletal Sciences at the University of Oxford. We performed a review of all published RCTs conducted within OCTRU, with particular emphasis on trial methodology, statistical study design and statistical analysis. Methods Studies were considered eligible if they were: RCTs conducted by OCTRU, have been completed and disseminated their primary results. Studies were ineligible if they were: a pilot or feasibility trial, a simulation study, a secondary analysis of an existing RCT, or a phase I trial. Phase II trials were considered if they were randomised. We performed double data extraction of all fields for all eligible trials. General trial information, such as primary disease area, main funding source, sample size, trial design and analysis information (e.g. number of study outcomes and analyses performed), were extracted and summarised. An analysis was defined as any time a statistical model was fit or a corresponding statistical test (e.g. χ 2 test) and/or estimation of a parameter was performed. Results Of the 142 OCTRU studies registered & funded (as of June 2023), 70 were completed and written up and 27 were eligible at the time of this review. The rest were ongoing or found to be ineligible. Included studies were published between 2014 and 2023, the majority in the last 5 years (20/27, 74% published between 2020 and 2023). All trials were multi-centre, prospectively designed and referred to both a study protocol and sample size justification (usually a power calculation) in their published results. Most included studies had elements of what could be referred to as a ‘standard’ RCT; used a parallel group design (93%), powered with superiority question (26/27, 96%), had two randomised groups (23/27, 85%) or used an equal allocation ratio (25/27, 93%). The median sample size was 451 (interquartile range: 238–836). The median total number of analyses performed was 22 (Interquartile range: 14–30) with the most analyses performed within a single trial being 69. Eighty-one per cent (22/27) of trials had a primary outcome with either binary or continuous data. Linear mixed effects, linear regression or logistic regression was used as the primary analysis model in 74% of the 27 trials. All trials that included at least one analysis (26/27) featured at least one additional analysis on the primary outcome, the most popular additional analyses were on an alternative population (for example a per-protocol population), occurring in 20/27, 74% of all trials, or a subgroup (18/27, 67%)). Conclusions This review summarises RCTs conducted by one academic UKCRC-registered CTU with a focus on the trial design and statistical analysis. We found most RCTs adopted what could be considered a ‘standard’ design, using appropriate, but not complex, analysis methods. Consideration of variation in practice across other groups, both academic and commercial, through a larger review would allow systematic exploration of methodological differences, less common study design usage, and would enable a fuller understanding of practice, outcomes, and methods used in different clinical areas and contexts.